A Double-Blind Randomized Controlled Trial on the Effectiveness of Acceptance and Commitment Therapy on Resiliency, Anxiety and Perceived Stress in Women with Breast Cancer - Varshosaz, Pardis; Kalantari, Farazmand (International Journal of Applied Behavioral Sciences, 2018)
Introduction: Growing evidence shows that mindfulness based on self-help interventions have advantages for physical and psychological health in different populations. The mindfulness based emotional balance is a new program and efficacy of which has not been investigated in self-help format. Methods: This study was a randomized control trial (RCT) with wait-list control. After screening and applying inclusion and exclusion criteria eighty students of Kermanshah University of medical sciences were assigned randomly to the mindfulness-based emotional balance self-help or the wait list control group. Anxiety, depression, stress, and mindfulness were measured prior to the intervention after the intervention, and two-month after end of intervention as follow-up. DASS-21 and MAAS were used. Results: Significant decrease in anxiety, depression, and stress in addition to a significant increase in mindfulness in the experimental group in the posttest. However, there were no significant changes in any of the aforesaid measures in the wait list control group. The resultant benefits were persistent in the two-month follow-up. Conclusion: Based on the results of this study, this type of treatment can be used as an efficient and cost-effective method to improve psychological problems such as stress, depression and anxiety. Declaration of Interest: None